Associations between insurance-related affordable care act policy changes with HPV vaccine completion - Hawkins, Summer Sherburne (BMC Public Health, 2021)
BACKGROUND: Although all 11- or 12-year-olds in the US were recommended to receive a 3-dose series of the human papillomavirus (HPV) vaccine within a 12-month period prior to 2016, rates of completion of the HPV vaccine series remained suboptimal. The effects of the Affordable Care Act (ACA), including private insurance coverage with no cost-sharing and health insurance expansions, on HPV vaccine completion are largely unknown. The aim of this study was to examine the associations between the ACA’s 2010 provisions and 2014 insurance expansions with HPV vaccine completion by sex and health insurance type. METHODS: Using 2009–2015 public and private health insurance claims from Maine, New Hampshire, and Massachusetts, we identified 9-to-26-year-olds who had at least one HPV vaccine dose. We conducted a logistic regression model to examine the associations between the ACA policy changes with HPV vaccine completion (defined as receiving a 3-dose series within 12 months from the date of initiation) as well as interactions by sex and health insurance type. RESULTS: Over the study period, among females and males who initiated the HPV vaccine, 27.6 and 28.0%, respectively, completed the series within 12 months. Among females, the 2010 ACA provision was associated with a 4.3 percentage point increases in HPV vaccine completion for the privately-insured (0.043; 95% CI: 0.036–0.061) and a 5.7 percentage point increase for Medicaid enrollees (0.057; 95% CI: 0.032–0.081). The 2014 health insurance expansions were associated with a 9.4 percentage point increase in vaccine completion for females with private insurance (0.094; 95% CI: 0.082–0.107) and a 8.5 percentage point increase for Medicaid enrollees (0.085; 95% CI: 0.068–0.102). Among males, the 2014 ACA reforms were associated with a 5.1 percentage point increase in HPV vaccine completion for the privately-insured (0.051; 95% CI: 0.039–0.063) and a 3.4 percentage point increase for Medicaid enrollees (0.034; 95% CI: 0.017–0.050). In a sensitivity analysis, findings were similar with HPV vaccine completion within 18 months. CONCLUSIONS: Despite low HPV vaccine completion overall, both sets of ACA provisions were associated with increases in completion among females and males. Our results suggest that expanding Medicaid across the remaining states could increase HPV vaccine completion among publicly-insured youth and prevent HPV-related cancers. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10328-4.